Problem Based Learning: Improve Critical Thinking Skills for Long Life Learning - Dinda Karunia Putri; Rusly Hidayah; Yohanan Didik Yuwono (Postgraduate, University of Mataram, 2023)
This study aims to increase the students' critical thinking. The subjects of this study were 37 students of XI-Science E from Senior High School 2 Tuban, who used the Problem Based Learning (PBL) model. This research was a Class Action Research (CAR) used interviews with chemistry teachers at Senior High School 2 Tuban, the observation’s instruments were used student activity sheet and posttest questions to measure the students’ critical thinking skills. The research was conducted in two cycles with a total of four meetings. The data analyzed descriptively and obtained were learning using PBL between cycles 1 and 2 experienced increase in activity of paying attention to teacher explanations, giving opinions, investigating, analyzing solutions, and students' critical thinking skills increased based on the analysis of posttest scores in cycles 1 and 2. The mean value in cycle 1 of the interpretation indicator was 45 while in cycle 2 it went up to 97, in the inference indicator the average of cycle 1 was 58 while cycle 2 increased to 98 and the analysis indicator in cycle 1 had an average value of 53 while cycle 2 was 81. The completeness of students was seen by the percentage of students whose posttest scores in cycle 2 reached KKM, namely interpretation of 97% (35) of students complete, inference of 95% (35) students complete, and analysis as much as 86% (32) students completed.